Practicas de la ingeniería - Dominique Vinck (Revue d'anthropologie des connaissances)
The article highlights the main contributions of the social studies of engineering, and reports on the historical shaping of its practices and knowledge. It then reviews the state of the art of our knowledge on the production and mobilization of formal and informal knowledge in engineering: knowledge received in training; computational, modelling and formalizing thinking; types of knowledge, including their socio-technical nature; knowledge of coordination, prescription and communication; their socio-political constitution and the challenges of innovation.